Epigenetic Therapy in Lung Cancer – Role of microRNAs - Rothschild, Sacha I. (Frontiers in Oncology, 2013)
Lung cancer is the leading cause of cancer deaths worldwide. microRNAs (miRNAs) are a class of small non-coding RNA species that have been implicated in the control of many fundamental cellular and physiological processes such as cellular differentiation, proliferation, apoptosis, and stem cell maintenance. Some miRNAs have been categorized as “oncomiRs” as opposed to “tumor suppressor miRs.” This review focuses on the role of miRNAs in the lung cancer carcinogenesis and their potential as diagnostic, prognostic, or predictive markers.